2009
DOI: 10.1523/jneurosci.6183-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Enigmatic Central Canal Contacting Cells: Immature Neurons in “Standby Mode”?

Abstract: The region that surrounds the central canal of the spinal cord derives from the neural tube and retains a substantial degree of plasticity. In turtles, this region is a neurogenic niche where newborn neurons coexist with precursors, a fact that may be related with the endogenous repair capabilities of low vertebrates. Immunohistochemical evidence suggests that the ependyma of the mammalian spinal cord may contain cells with similar properties, but their actual nature remains unsolved. Here, we combined immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
133
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(159 citation statements)
references
References 58 publications
22
133
4
Order By: Relevance
“…However, despite this evolutionary conservation, their function has not yet been fully elucidated. Gata2 + neurons of the central canal in newborn and young mice exhibit molecular and physiological characteristics of immature neurons, in agreement with previous observations (Stoeckel et al, 2003;Marichal et al, 2009;Sabourin et al, 2009;Orts-Del'Immagine et al, 2014Kútna et al, 2014).…”
Section: Heterochronic Development Of Csf-cns In Vertebratessupporting
confidence: 92%
See 2 more Smart Citations
“…However, despite this evolutionary conservation, their function has not yet been fully elucidated. Gata2 + neurons of the central canal in newborn and young mice exhibit molecular and physiological characteristics of immature neurons, in agreement with previous observations (Stoeckel et al, 2003;Marichal et al, 2009;Sabourin et al, 2009;Orts-Del'Immagine et al, 2014Kútna et al, 2014).…”
Section: Heterochronic Development Of Csf-cns In Vertebratessupporting
confidence: 92%
“…S1J-N). Whole-cell GFP labeling identified these cells as the cerebrospinal fluidcontacting neurons of the central canal (CSF-cNs) VighTeichmann, 1971, 1998;Vigh et al, 1977;Stoeckel et al, 2003;Marichal et al, 2009) (Fig. 1J-M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Marichal [34] brought immunohistochemical evidence that a subpopulation of ependymal cells exhibits features of immature neurons which are in "stand by mode". The functional role of such persistent proliferation activity in the spinal cord is not fully understood but anyway could contribute to the plasticity of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Also there are instances of indirect injury to the adult spinal cord, such as dorsal rhizotomy (cutting of the dorsal root at the cervical spinal level) in which neurogenesis is observed in the dorsal horn at the corresponding spinal level (Vessal, Aycock et al 2007). Recent papers showed that in non-injured, intact adult spinal cords, immature neurons can be found in the area surrounding the central canal (Shechter, Ziv et al 2007;Marichal, Garcia et al 2009), but also throughout the spinal cord, with a preferential dorsal gray matter localization and exclusive GABAergic phenotype (Shechter, Ziv et al 2007;Shechter, Baruch et al 2011). The exact roles of these immature neurons in the healthy spinal cord have not been determined, but may indicate physiological roles for new GABAergic neurons in nociception (Shechter, Baruch et al 2011), and also for movement.…”
Section: Neurogenesis In the Adult Spinal Cordmentioning
confidence: 99%